The homological functors of 2-generator 2-groups of nilpotency class two of type 2 / Nor Haniza Sarmin, Nor Muhainiah Mohd. Ali and Mohd. Sham Mohamad - Sarmin, Nor Haniza; Mohd. Ali, Nor Muhainiah; Mohamad, Mohd. Sham (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
The classification of 2-generator 2-groups of nilpotency class two and their nonabelian tensor squares given by Kappe, Sarmin and Visscher in 1999 will be used throughout this research. The homological functors of all 2-generator 2-groups of nilpotency class two of Type 2 will be given in this paper. Furthermore, the nonabelian tensor squares and homological functors of one specific group of Type 2 will also be computed. The results of these computations will be verified by Groups, Algorithms and Programming (GAP) software.